2012
DOI: 10.1039/c2ce06409j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of surface-modified monoclinic ZrO2 nanoparticles using supercritical water

Abstract: We succeeded in simple and rapid synthesis of surface-modified monoclinic ZrO 2 nanoparticles using a supercritical hydrothermal method. The precursor Zr(OH) 4 was treated in the presence of various surface modifiers with carboxyl group (-COOH) in a batch-type reactor at 400 C for 10 min. Oleic, sebacic, dodecanedioic, and 12-aminododecanoic acids were used as surface modifiers. Addition of surface modifiers resulted in smaller particle (crystallite) sizes than the unmodified nanoparticles, suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 39 publications
6
52
0
Order By: Relevance
“…The AN800 product had spherical particles, and this morphology appeared to have been retained from that of the AG product. The morphologies of the products were similar to those of the monoclinic ZrO 2 nanocrystals found in our previous studies [21,22]. However, the annealing process clearly changed the particle sizes, which were approximately 1.5 times higher after the annealing treatment.…”
Section: Productssupporting
confidence: 69%
See 3 more Smart Citations
“…The AN800 product had spherical particles, and this morphology appeared to have been retained from that of the AG product. The morphologies of the products were similar to those of the monoclinic ZrO 2 nanocrystals found in our previous studies [21,22]. However, the annealing process clearly changed the particle sizes, which were approximately 1.5 times higher after the annealing treatment.…”
Section: Productssupporting
confidence: 69%
“…Similarly increased lattice sizes were also observed in our previous studies of metal oxide nanocrystals [18][19][20][21][22]. Comprehensive experimental studies of metal oxide nanocrystals have also shown that the lattice constant tends to increase as the particle size decreases [26][27][28].…”
Section: Productssupporting
confidence: 63%
See 2 more Smart Citations
“…16,42 Water is believed to increase the solubility of the formed ZrO2 precipitates during synthesis which facilitates the effective operation of dissolution and precipitation leading to the more stable m-ZrO2. 16,[43][44][45] To assess the role of water in in our synthesis method, distilled water was added to the propoxide precursor. From the resulting XRD and TEM analysis it is clear that the presence of water does not lead to a change in crystal phase of ZrO2 (Table 3, Figure 4 and SAED Figure 5B).…”
Section: Resultsmentioning
confidence: 99%